Strategies for Using Peer‐assisted Learning Effectively in an Undergraduate Bioinformatics Course. Issue 1 (28th January 2013) - Shapiro, Casey; Ayon, Carlos; Moberg‐Parker, Jordan; Levis‐Fitzgerald, Marc; Sanders, Erin R.
<x xml:space="preserve">Abstract</x> This study used a mixed methods approach to evaluate hybrid peer‐assisted learning approaches incorporated into a bioinformatics tutorial for a genome annotation research project. Quantitative and qualitative data were collected from undergraduates who enrolled in a research‐based laboratory course during two different academic terms at UCLA. Findings indicate that a critical feature of the peer‐assisted learning approach is to have near‐peer leaders with genome annotation experience, allowing them to communicate technical and conceptual aspects of the process in the context of a research project (a.k.a., the "big picture"). These characteristics are important for creating connections between the wet lab experiments and the computer lab activities, engendering excitement about the research project and fostering engagement in bioinformatics as a discipline. Likewise, it is essential to couple tutorial training in genome annotation with appropriate instructional materials, providing detailed, step‐by‐step instructions for database navigation. Finally, the assessment results support this hybrid peer‐assisted learning approach as a model for undergraduates to successfully learn bioinformatics in a course setting. © 2012 by The International Union of Biochemistry and Molecular Biology, 41(1):24–33, 2013